ملامح التقنيات الكيميائية لعلماء المسلمين في الأندلس (316-422هـ): Features of the Chemical Techniques of Muslim Scholars in Andalusia from 928 - 1031AD - Mousa, Faraj Murajia; Abdul Hamid, Faisal @ Ahmad Faisal (Journal Al-Muqaddimah, 2023)
This paper discusses the efforts made by Muslim scholars in the field of chemical sciences in Andalusia. The main aims of this paper are to highlight the types of chemical compounds and to clarify the methods of experiments in producing the chemicals. To achieve these goals, the intelligence of Muslim scientists who laid the foundations of the science of experience must be studied. In this study, it is discovered that Muslim scholars contributed to laying the foundations of global civilization during the Middle Ages. Therefore, understanding their contributions in this regard is of great importance as clearly deliberated in their scientific books and manuscripts. This study went further to expose the abundance of scientific production achieved during the time of the Umayyad Caliphate in Andalusia. The researcher used the narrative approach by referring to historical sources. The findings reveal that Muslim scholars in producing various scientific knowledge relied on various techniques and experiments in an inductive and deductive manner. The finding of this study further shows that Muslim scholars avoided the science of chemistry, superstitions, magic and invents their own in the light of Islamic sources and experiments by using calcium hydroxide, caustic soda, and ammonia solution. They also highlighted on their mixture, interactions and properties and explained how they unite and combine with acids to produce salts, and they were able to differentiate between potassium, salts, and sodium. Hence, these are the methods employed by Muslim scholars in laying the foundations for scientific progress.